Sociolinguistic Situation of Turkic Ethnicities Deported to Kazakhstan - Tazhibayeva, Saule; Nevskaya, Irina (Turkic Studies Journal, 2021)
The article discusses the sociolinguistic situation of the Kazakhstani Turkic communities deported to Kazakhstan in the 1930s and 1940s. Different Turkic ethnicities had been forcibly relocated from their historical places of living to Southern regions of Kazakhstan. The results of the research are based on a sociolinguistic survey and oral interviews that have been conducted in 2013-2018 within the framework of the international project ‘Interaction of languages and cultures in post-Soviet Kazakhstan’, funded by the Volkswagen Foundation. A free-license online database with the obtained sociolinguistic data was created, allowing filtering the data according to 191 parameters. Special attention is paid to Azeri and Meskhetian Turks belonging to most numerous Turkic ethnic groups living in contemporary Kazakhstan. Azeri people were allowed to return to their historical homeland in the 1960s. The Meskhetian and Hemshilli Turkish communities did not get permission to return to the regions of their historical settlement in Georgia. They found the second homeland in Kazakhstan got integrated into its cultural and socioeconomic life.